Efek Metabolit Susu Fermentasi terhadap proid pada Tikus Sprague Dawley=The Effect of Fermented Milk Metabolites to Lipid Profile in Sprague Dawley Rats - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Probiotic products such as fermented milk had been widely distributed in the market and proved to have beneficial health effect, previous research indicated that rats fed with milk products supplemented with indigenous Lactabacillus Dad 13 cells (LD13) capable of reducing cholesterol level. However, such products posses several problems such as reduction of cell viability and organoleptic stability, and requirement of low temperature during storage . Therefore it was necessary to study the effect of pasteurized and sterilised fermented milk metabolites on cholesterol reduction in order to develop more stable products. The research was done to study the effect of pasteurised and sterilised fermented milk with Lactobacillus Dadl3 on cholesterol lowering capability in vivo. The study was done by using 70 male rats 2-months old. The rats were divided into ten groups and fed ad libitum with 2 different diets (Standard AIN-93 and hyphercholesterol diets). During the first week rats were fed with standard diet followed by hyper-cholesterol diet for a week. Lipid profile were measured at the end of the week. When experiments started, rats were assigned to standard fed groups and hypercholesterol fed group. Both of them were treated with diet intervention for 4 weeks. During diet intervention period, the rats were given water (placebo), skim milk 10%, sterilised fermented milk (SFM), pasteurized fermented milk (PFM), commercial fermented milk (CAL). At the end of the treatments, lipid profiles were analysed. The results showed that pasteurised fermented milk (PFM) and sterilised fermented milk (SFM) reduced total cholesterol level by 38.5% - 43.5%, low density lipoprotein (LDL) by 7.08% - 8.5%, high density lipoprotein (HDL) by 50.04% - 56%, and triglyceride (TG) by 31.06% -34.75%. These indicated that metabolits of SFM capable of reducing cholesterol level in vivo. Keywords: hypocholesterolemic - Lactobaccilus so Dadl3 -pasteurised fermented milk (PFM) and sterilised fermented milk (SFM).